PENGARUH INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN MOP BEAUTY BY TASYA FARASYA MELALUI BRAND AWARENESS - Rikeu Hafshah Hafizhah, (2022)
This research is a quantitative study to determine the effect of influencer on purchase decisions, the effect of brand awareness on purchasing decisions, the effect of influencer on brand awareness, and the effect of influencer indirectly on purchasing decision through brand awareness. The population of this study is an unknown number of consumers of MOP Beauty by Tasya Farasya products who are domiciled in DKI Jakarta. The sample used is 100 respondents. The sampling technique used non-probability sampling with purposive sampling method. Data collection in this study was carried out using an online questionnaire. This study uses the SEM method with the software used is SmartPLS 3.2.9. The research obtained the results that the influencer variable has a positive and significant effect on purchasing decisions with an original sample value of 0.399. Brand awareness has a positive and significant effect on purchasing decisions with an original sample value of 0.525. Influencer has a positive and significant effect on brand awareness with an original sample value of 0.873. Influencer indirectly has a positive and significant effect on purchasing decisions through brand awareness with an original sample value of 0.458.